9(m-1)=-18

Simple and best practice solution for 9(m-1)=-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(m-1)=-18 equation:


Simplifying
9(m + -1) = -18

Reorder the terms:
9(-1 + m) = -18
(-1 * 9 + m * 9) = -18
(-9 + 9m) = -18

Solving
-9 + 9m = -18

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 9m = -18 + 9

Combine like terms: -9 + 9 = 0
0 + 9m = -18 + 9
9m = -18 + 9

Combine like terms: -18 + 9 = -9
9m = -9

Divide each side by '9'.
m = -1

Simplifying
m = -1

See similar equations:

| 5(m+2)=25 | | 8(x-4)=48 | | 16n+20k-11n+13= | | 35=7+11+c | | 0.30x+0.04(50)=0.15(70) | | 2(x+4)=5x-5 | | 11x=40+(6x+4) | | 2(x+4)=7-(3+x) | | 9x-14=7x+2 | | 7-2(a-1)=6-a | | 5p-10=20 | | 3x^2=2x^2-9x | | 3-|x+1|=|x+1|+|-x-3| | | 6x+xy= | | 5w-6=24 | | 9z-9=27 | | 10M-11=69 | | 7x-12=13+2x | | 6x+3=4x+10 | | 5x-9=16+10x | | 4xy+-9x= | | 3x-10=8-2x | | 6x-245=360 | | 9m-5=40-6m | | 4x-11=2x-25 | | 6x-245+210-x+x+x=360 | | 10s-3=67 | | (11b-7)-5(2b+2)=-5 | | -2b(2b+3)+(5b-6)=0 | | 4x=1-16 | | 6x-245+210-x+x=360 | | 3(x-2)/5+2(x-1)/10=x-4/2 |

Equations solver categories